2022
DOI: 10.1007/s44197-022-00035-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Alcohol Treatment Access and Harm Prevention in West Africa: Reports from NGOs and Community-Based Organizations

Abstract: Background Recent research highlights how the COVID-19 pandemic has significantly impacted alcohol consumption patterns, yet research thus far has largely overlooked the experience in West Africa. Research also has not addressed how the COVID-19 pandemic has affected access to alcohol treatment, support, and alcohol harm prevention. This study addresses this research gap in West Africa, a low-resource setting with a very high burden of alcohol harm. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…They found that the median prevalence of reported youth drinking was 52% (Francis et al, 2014). Other recent studies on alcohol in East Africa have focused on specific countries and populations, including research on the prevalence of alcohol misuse among adolescent girls and young women in Uganda (Mayanja et al, 2020); alcohol use linked to child physical abuse in slums in Kampala, Uganda (Culbreth et al, 2021;Swahn et al, 2017); sexual-related harm in Kampala, Uganda (Swahn, Balenger, Umenze, Aneja et al, 2022); intimate partner violence and gender-based violence, HIV and sexually transmitted infections (STIs) in Kampala, Uganda (Culbreth et al, 2021;Culbreth et al, 2020;; the prevalence and key drivers of adult alcohol use in rural Kenya (Takahashi et al, 2017); alcohol use among injured patients in Moshi, Tanzania; alcohol among youth in urban Tanzania (Sommer et al, 2021); and drug use among youth in Rwanda (Kanyoni et al, 2015). Because of this fragmented approach to alcohol research in East Africa, researchers have not yet comprehensively assessed or identified priorities for the prevention of alcohol-related harm in this region although there has been a call for the development of an alcohol research agenda (Swahn et al, 2023).…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…They found that the median prevalence of reported youth drinking was 52% (Francis et al, 2014). Other recent studies on alcohol in East Africa have focused on specific countries and populations, including research on the prevalence of alcohol misuse among adolescent girls and young women in Uganda (Mayanja et al, 2020); alcohol use linked to child physical abuse in slums in Kampala, Uganda (Culbreth et al, 2021;Swahn et al, 2017); sexual-related harm in Kampala, Uganda (Swahn, Balenger, Umenze, Aneja et al, 2022); intimate partner violence and gender-based violence, HIV and sexually transmitted infections (STIs) in Kampala, Uganda (Culbreth et al, 2021;Culbreth et al, 2020;; the prevalence and key drivers of adult alcohol use in rural Kenya (Takahashi et al, 2017); alcohol use among injured patients in Moshi, Tanzania; alcohol among youth in urban Tanzania (Sommer et al, 2021); and drug use among youth in Rwanda (Kanyoni et al, 2015). Because of this fragmented approach to alcohol research in East Africa, researchers have not yet comprehensively assessed or identified priorities for the prevention of alcohol-related harm in this region although there has been a call for the development of an alcohol research agenda (Swahn et al, 2023).…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…Temporal constraints may account, in part, for the paucity of COVID-19 literature identified, as pandemic-related delays in the conduct and peer review of primary research may have precluded publication prior to our April 2022 search date. Additionally, our review eligibility requirement of service-level barriers meant that studies reporting only policy-level barriers related to the pandemic more broadly, such as lockdowns (7,161), were ineligible for inclusion. Strategies to mitigate the effects of COVID-19 by substance use treatment facilities early in the pandemic were reported in a scoping review (12).…”
Section: Impact Of Covid-19 On Pau Treatment Accessibilitymentioning
confidence: 99%
“…However, there is limited research on the impact of COVID‐19 on patients undergoing treatment for AUD or those seeking recovery from AUD. Several studies have reported that accessibility to addiction treatment declined in the early stages of the pandemic (Balhara et al, 2020; Swahn et al, 2022). For example, during the lockdown in India in March 2020, a survey of 72 AUD patients was conducted by phone.…”
Section: Introductionmentioning
confidence: 99%